Different Infective and Non-Infective Etiology of Exudative Pleural Fluid Effusion: Experience of 50 Cases in Bangladesh (Bangladesh Journal of Medical Microbiology, 2023)
Background: Several diseases are responsible for the causation of exudative pleural fluid effusion among patients. Objective: The purpose of the present study was to identify the etiologies of exudative pleural fluid effusion. Methodology: This cross-sectional study was carried out at medicine indoor department of Sylhet MAG Osmani Medical College Hospital, Sylhet over a period of six month from October 2009 to March 2010. Patients who were admitted with pleural effusion were selected as the study population. Pleural fluid was collected by a physician. The laboratory tests were performed in the Department of Laboratory medicine of the Hospital. The different etiologies were determined by the different diagnostic tests. Results: A total of 50 cases were selected consecutively in the study. Out of 50 patients, 28.0% was in the range of 41 to 50 years followed by 26.0% between 31 to 40 years. Tuberculosis was the most common cause of exudative pleural effusion and among 50 cases of effusion 30 were due to tuberculosis (60%). Malignancy was found as the 2nd common cause of exudative pleural effusion (24.0%). Pneumonia was found as the 3rd common cause of exudative pleural effusion (10.0%). Conclusion: In conclusion tuberculosis is the most common cause of exudative pleural effusion followed by malignancy.Bangladesh Journal of Medical Microbiology, January 2023;17(1):10-14